ChemInform Abstract: 1, 4‐Addition of TMSCCl3 to Nitroalkenes: Efficient Reaction Conditions and Mechanistic Understanding. Issue 51 (23rd December 2014) - Wu, Na; Wahl, Benoit; Woodward, Simon; Lewis, William
Abstract Nitro substituted electron deficient Michael acceptors undergo an efficient 1, 4‐addition reaction with trimethyl(trichloromethyl)silane in the presence of Bu4NPh2SiF2 as catalyst.